Answer:
X=5
Step-by-step explanation:
Cancel equal terms remove parentheses.
Move the constant to the right.
Add the numbers.
Divide by 3 on both side. and X=5
Hope this helps
Answer: 18x^3-9x^2+21x
Solution:
3x(6x^2-3x+7)=
Applying the distributive property in the multiplication to eliminate the parentheses:
(3x)(6x^2)+(3x)(-3x)+(3x)(7)=
(3*6)x^(1+2)+3*(-3)x^(1+1)+(3*7)x=
18x^3-9x^2+21x
Answer:
a
the first answer
Step-by-step explanation:
Answer:
9
Step-by-step explanation:
4+5 is equal to 9.
First fine f(2).
f(2) = 2*2 - 3
f(2) = 4 - 3
f(2) = 1
Now g(3).
g(3) = 4*3
g(3) = 12
Now subtract 1 - 12 = -11
-11 is your answer.